1997
DOI: 10.1016/s0969-8051(97)00007-3
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Metabolism of [N-methyl-11C]-m-hydroxyephedrine in the Rat

Abstract: Biodistribution and metabolism of [N-methyl-11C]m-hydroxyephedrine ([11C]mHED), an analogue of noradrenaline, were assessed in rats. Pretreatment with desipramine, an uptake blocker, reduced uptake of radioactivity in myocardium but not in lung, liver, kidney, and muscle. Brain uptake was negligible. HPLC showed six radioactive metabolites in plasma and liver but none in myocardium. Co-injection of unlabelled mHED or metaraminol with [11C]mHED demonstrated no difference between the in vivo binding potentials f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
26
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 0 publications
5
26
1
Order By: Relevance
“…Moreover, HED is resistant to the NE-metabolizing enzymes monoamine oxidase (MAO) and catechol-Omethyltransferase (9). Characterization studies of HED have demonstrated dependence of retention on the functionality and availability of NET (12,13), confirming specificity in myocardium, spleen, and adrenal glands (9,11,14). Pharmacokinetic studies performed in animal models and isolated organ systems (2,9,11,15) have implied a correlation between NE concentration and clearance rate of HED (2,15).…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…Moreover, HED is resistant to the NE-metabolizing enzymes monoamine oxidase (MAO) and catechol-Omethyltransferase (9). Characterization studies of HED have demonstrated dependence of retention on the functionality and availability of NET (12,13), confirming specificity in myocardium, spleen, and adrenal glands (9,11,14). Pharmacokinetic studies performed in animal models and isolated organ systems (2,9,11,15) have implied a correlation between NE concentration and clearance rate of HED (2,15).…”
mentioning
confidence: 89%
“…Characterization studies of HED have demonstrated dependence of retention on the functionality and availability of NET (12,13), confirming specificity in myocardium, spleen, and adrenal glands (9,11,14). Pharmacokinetic studies performed in animal models and isolated organ systems (2,9,11,15) have implied a correlation between NE concentration and clearance rate of HED (2,15). Metabolite analyses in rats, guinea pigs, dogs, and humans revealed that metabolites detected in plasma and liver are not present in cardiac tissue, facilitating qualitative image analysis and clinical interpretation (9,11,16).…”
mentioning
confidence: 89%
See 3 more Smart Citations